ANALISIS ACCOUNTS RECEIVABLE TURNOVER DAN FIXED ASSETS RATIO TERHADAP PROFITABILITAS PADA SEKTOR BARANG KONSUMSI - Agus Munandar; Fitriyani Khasanah; Winda Amelia (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
The purpose of research in this scientific journal is to examine and analyze in depth the relationship between receivables and fixed asset turnover with profitability in consumer goods companies on the IDX for the 2018-2020 period. The research method used in this scientific journal is a quantitative method where quantitative methods allow objects to be analyzed to make them look more real. As the basis for this study, we use financial reporting tables for consumer goods. The data in this study is sourced from the consumer goods manufacturing industry per year from 2018 to 2020. This scientific journal examines 3 companies that will be included in the research by collecting financial data released by the IDX for 3 consecutive years. The results of this scientific journal research show that receivables and fixed asset turnover affect the profitability of consumer goods companies on the Indonesia Stock Exchange during the 2018-2020 period. Accounts receivable turnover partially affects the profits of consumer goods sector companies on the IDX for the 2018 - 2020 period. Fixed assets have a partial and insignificant effect on company profits.